Comparison of dosimetric parameters in the treatment planning of magnetic resonance imaging–based intracavitary image-guided adaptive brachytherapy with and without optimization using the central shielding technique - Nishikawa, Ryo; Yoshida, Kenji; Ebina, Yasuhiko; Omoteda, Mayumi; Miyawaki, Daisuke; Ishihara, Takeaki; Ejima, Yasuo; Akasaka, Hiroaki; Satoh, Hitoaki; Kyotani, Katsusuke; Takahashi, Satoru; Sasaki, Ryohei (Journal of radiation research, 2018)
This study aimed to compare dosimetric parameters between non-optimized and optimized treatment planning (NOP and OP, respectively) of magnetic resonance imaging (MRI) -based intracavitary (IC) image-guided adaptive brachytherapy (IGABT) using the central shielding (CS) technique for cervical cancer. Fifty-three patients treated with external beam radiotherapy using CS and MRI-based IGABT with the IC approach alone were evaluated. The total high-risk clinical target volume (HR-CTV) D90 was aimed at >70 Gy equivalent dose in 2 Gy fractions (EQD2). In the small HR-CTV group (≤30 cm3), the mean D90s for NOP/OP were 98.6/80.7 Gy. In the large (30.1-40 cm3) and extensive (>40 cm3) HR-CTV groups, the mean D90s were 81.9/77.5 and 71.1/73.6 Gy, respectively. The mean D2cc values for organs at risks (OARs) in OP were acceptable in all groups, despite the high bladder D2cc in the NOP. The correlation between HR-CTV at first brachytherapy (BT) and NOP D90 was stronger than that between HR-CTV at first BT and OP D90. The targeted HR-CTV D90 and dose constraints of D2cc for OARs were both achieved in 16 NOP/47 OP patients for the bladder, 39/50 for the rectum, and 47/50 for the sigmoid colon (P < 0.001, P = 0.007, and P = 0.34, respectively). For small tumors, the role of optimization was to reduce the D2cc for OARs while maintaining the targeted D90. However, optimization was of limited value for extensive tumors. Methods of optimization in IGABT with CS for cervical cancer should be standardized while considering its effectiveness and limitations.